Comprehensive Profiling of Lysine Acetylome in Baculovirus Infected Silkworm (Bombyx mori) Cells. Issue 1 (15th January 2018) - Hu, Dongbing; Xue, Shengjie; Zhao, Cui; Wei, Ming; Yan, Huihui; Quan, Yanping; Yu, Wei
Abstract: Bombyx mori is one of the key lepidopteran model species, and is economically important for silk production and proteinaceous drug expression. Baculovirus and insect host are important natural biological models for studying host–pathogen interactions. The impact of Bombyx mori nucleopolyhedrovirus (BmNPV) infection on the proteome and acetylome of Bombyx mori ovarian (BmN) cells are explored to facilitate a better understanding of infection‐driven interactions between BmNPV and host in vitro. The proteome and acetylome are profiled through six‐plex Tandem mass tag (TMT) labeling‐based quantitative proteomics. A total of 4194 host proteins are quantified, of which 33 are upregulated and 47 are downregulated in BmN cells at 36 h post‐infection. Based on the proteome, quantifiable differential Kac proteins are identified and functionally annotated to gene expression regulation, energy metabolism, substance synthesis, and metabolism after BmNPV infection. Altogether, 644 Kac sites in 431 host proteins and 39 Kac sites in 22 viral proteins are identified and quantified in infected BmN cells. Our study demonstrates that BmNPV infection globally impacts the proteome and acetylome of BmN cells. The viral proteins are also acetylated by the host acetyltransferase. Protein acetylation is essential for cellular self‐regulation and response to virus infection. This study provides new insights for understanding the host–virus interaction mechanisms, and the role of acetylation in BmN cellular response to viral infection.